Training with a heavy puck elicits a higher increase of shooting speed than unloaded training in midget ice hockey players - Novak, D.; Loskot, J.; Roczniok, R.; Opath, L.; Stastny, P. (Journal of Human Kinetics, 2022)
A method of load variability is a common way of developing specific skills in various sports, however, not explored considering the use of different ice-hockey pucks. Therefore, the purpose of this study was to compare shooting speed, shooting accuracy, and handgrip strength changes after training with variable training loads (lighter 60g pucks and heavier 260g pucks) in the wrist shot and snapshot. Sixteen male ice hockey players (13.62±0.35y; 167.67±7.71cm; 53.87±7.55kg) were subjected to a 12 week experiment during which they trained six weeks with a light puck and six weeks with a heavy puck and were tested for shooting speed, shooting accuracy and handgrip strength. The variable load training increased shooting speed (the long hand snapshot by 7.4%, the shorthand snapshot by 8.5%, and the wrist shot by 13%), shooting accuracy (by 14%), and handgrip strength (by 8.7%) of the bottom hand; all at p<0.001. Training with heavy pucks was more effective (d=0.50-0.86) than training with lighter pucks (d=23-25) for increasing puck speed. Shooting accuracy was increased by variable load training with a similar effect of heavy and light puck training. The variable training load had a positive effect on shooting speed and accuracy and the use of a heavier load was more effective than using the unloaded puck. Variable load shooting training in youth ice-hockey players is more effective with heavier pucks than lighter ones, and the improvements are greater in players with better shooting skills.